Aerosol-generating otolaryngology procedures and the need for enhanced PPE during the COVID-19 pandemic: a literature review - Paul Mick; Russell Murphy (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Adequate personal protective equipment is needed to reduce the rate of transmission of COVID-19 to health care workers. Otolaryngology groups are recommending a higher level of personal protective equipment for aerosol-generating procedures than public health agencies. The objective of the review was to provide evidence that a.) demonstrates which otolaryngology procedures are aerosol-generating, and that b.) clarifies whether the higher level of PPE advocated by otolaryngology groups is justified. Main body Health care workers in China who performed tracheotomy during the SARS-CoV-1 epidemic had 4.15 times greater odds of contracting the virus than controls who did not perform tracheotomy (95% CI 2.75–7.54). No other studies provide direct epidemiological evidence of increased aerosolized transmission of viruses during otolaryngology procedures. Experimental evidence has shown that electrocautery, advanced energy devices, open suctioning, and drilling can create aerosolized biological particles. The viral load of COVID-19 is highest in the upper aerodigestive tract, increasing the likelihood that aerosols generated during procedures of the upper aerodigestive tract of infected patients would carry viral material. Cough and normal breathing create aerosols which may increase the risk of transmission during outpatient procedures. A significant proportion of individuals infected with COVID-19 may not have symptoms, raising the likelihood of transmission of the disease to inadequately protected health care workers from patients who do not have probable or confirmed infection. Powered air purifying respirators, if used properly, provide a greater level of filtration than N95 masks and thus may reduce the risk of transmission. Conclusion Direct and indirect evidence suggests that a large number of otolaryngology-head and neck surgery procedures are aerosol generating. Otolaryngologists are likely at high risk of contracting COVID-19 during aerosol generating procedures because they are likely exposed to high viral loads in patients infected with the virus. Based on the precautionary principle, even though the evidence is not definitive, adopting enhanced personal protective equipment protocols is reasonable based on the evidence. Further research is needed to clarify the risk associated with performing various procedures during the COVID-19 pandemic, and the degree to which various personal protective equipment reduces the risk.